The use of crossword puzzle to improve vocabulary mastery (an experimental study at Ban Chokok school Thailand): Research Article - Adeela Pohloh; Sayid Ma'rifatulloh (Indonesian Reseacher for Language Learning and Teaching, 2023)
The objective of the research is to prove whether the use of crossword puzzle to improve vocabulary mastery. This pre-experimental study uses 24 students as a sample. They are grade VII of Ban chokok school. The procedure of this research consists of pretest, posttest. The result of the analysis shows that crossword puzzle to improve vocabulary mastery contributes greatly to increase the students’ vocabulary.The Researcher gave a pretest to students from 22 February 2022 until 28 February 2022. This is done before providing treatment to them. It is very important to measure students' skills in vocabulary. Pretest results are presented. The researcher administered post-test to was conducted after giving treatment to the students that presented It can be seen by the difference in the mean score between pre-test and post-test. The mean score of pre-test is 60 while in the post-test increases up to 100. Vocabulary has played an important role in mastering a language. It is believed that the more vocabulary mastered by students, the easier they are to develop the four language skills, i.e., listening, speaking, reading, and writing that vocabulary is an integrated part of a language. It is believed that the increase of a learner's vocabulary will affect better speaking and writing. Besides, their researches shows that the results of speaking and writing tests tend to increase. In short, vocabulary is the main core of language skills that provide the basis for how students use the language.